2004
DOI: 10.1073/pnas.0308044100
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of gene expression reveals function of the bZIP transcription factor HY5 in the UV-B response of Arabidopsis

Abstract: The light environment is a key factor that governs a multitude of developmental processes during the entire life cycle of plants. An important and increasing part of the incident sunlight encompasses a segment of the UV-B region (280 -320 nm) that is not entirely absorbed by the ozone layer in the stratosphere of the earth. This portion of the solar radiation, which inevitably reaches the sessile plants, can act both as an environmental stress factor and an informational signal. To identify Arabidopsis genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
547
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(576 citation statements)
references
References 40 publications
(39 reference statements)
18
547
3
2
Order By: Relevance
“…Recently, significant progress has been made in our understanding of the UV-B response pathway in Arabidopsis, which involves the UV-B photoreceptor UVR8 [9], two positive regulators COP1 [12] and HY5 [23], and two WD40-repeat-containing proteins, RUP1 and RUP2 that negatively regulate the pathway [24]. In this study, we identified BBX24 as a new negative regulator of UV-B responses in Arabidopsis.…”
Section: Lei Jiang Et Al 1053mentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, significant progress has been made in our understanding of the UV-B response pathway in Arabidopsis, which involves the UV-B photoreceptor UVR8 [9], two positive regulators COP1 [12] and HY5 [23], and two WD40-repeat-containing proteins, RUP1 and RUP2 that negatively regulate the pathway [24]. In this study, we identified BBX24 as a new negative regulator of UV-B responses in Arabidopsis.…”
Section: Lei Jiang Et Al 1053mentioning
confidence: 88%
“…The essential role of HY5 in UV-B signaling [23] encouraged us to examine whether BBX24 physically interacts with HY5. Full-length HY5 fused with the GAL4-DNA-binding domain interacted strongly with the BBX24 fused with the GAL4-activation domain in the yeast two-hybrid system ( Figure 3A).…”
Section: Bbx24 Interacts and Functions Antagonistically With Hy5 In Umentioning
confidence: 99%
See 1 more Smart Citation
“…Expression analysis of the cry1 and hy5 mutants during early light development or following a shift from darkness to light has been performed previously (Ma et al, 2001;Holm et al, 2002;Folta et al, 2003;Jiao et al, 2003;Ohgishi et al, 2004;Ulm et al, 2004). However, a direct comparison between our experiment and published results is difficult due to the usage of very different plant material.…”
Section: Cry1 and Hy5 Regulate A Large Number Of Genes In Response Tomentioning
confidence: 97%
“…Following monomerization, UVR8 accumulates in the nucleus and interacts with the positive regulator Constitutively Photomorphogenic 1 (COP1) [139][140][141][142], a WD40/RING-E3 ubiquitin ligase that in non-inductive conditions targets HY5 (Elongated Hypocotyl 5) for proteosome-dependent degradation [143]. HY5 is a key effector of UV-B protection and light photomorphogenic responses [144,145], and it is transcriptionally activated by UV-B in a UVR8-and COP1-dependent manner [146][147][148]. Other components of the UVR8 signalling pathway are repressor of UV-B photomorphogenesis 1 (RUP1) and RUP2.…”
Section: Uvr8-mediated Photomorphogenic Mechanisms In Response To Uv-mentioning
confidence: 99%